Barriers to sexual and reproductive health care faced by transgender and gender diverse people: a systematic review - Connor Luke Allen; Luke Muschialli; Åsa Nihlén; Anna Coates; Lianne M. Gonsalves (Reproductive Health)
Abstract Background Transgender (trans) and gender diverse people face significant obstacles when accessing sexual and reproductive health (SRH) services. This review aims to systematically identify and characterise the specific barriers to SRH barriers across a range of service domains. Methods A systematic literature search was carried across MEDLINE, CINAHL, Embase, PsycInfo and Global Index Medicus for studies published up until Aug 17, 2023. We included qualitative, quantitative and mixed-methods studies that illustrated which barriers to SRH services trans and gender diverse people face. Relevant data were extracted and examined using an inductive approach by which organic themes emerged across the SRH service domains. Quality assessment was carried out using the Critical Appraisal Skill Programme (CASP) checklists. Findings A total of 53 studies examining barriers to SRH services were deemed eligible for inclusion. This consisted of 20 studies relating to fertility care, two to abortion care, four to contraception, 15 to reproductive cancer screening, nine to antenatal, intrapartum and postnatal care and three spanning multiple domains of SRH. Eight studies were deemed to be moderate quality, the remaining 45 were high quality. 49 of the included studies were conducted exclusively in high-income countries. 40 studies were conducted from the perspectives of trans and gender diverse people, 10 from that of health providers whilst three incorporated both. Participants included for analysis ranged in age from 18 to 78 years. Domain specific and cross-cutting barriers were described throughout the included studies, including financial accessibility, lack of provider knowledge and education, limited information availability, systemic and interpersonal discrimination, cis-normative and gender biased health system practices and dysphoria associated with treatments and procedures. Interpretation Trans and gender diverse people face substantial barriers to SRH services that prohibit them from fully exercising their reproductive rights. The evidence collated by this review demonstrates that whilst some barriers are shared with cisgender women, trans and gender diverse people face unique barriers to accessing SRH services. Both systems- and individual-level reform is necessary to improve not only gender responsiveness but also gender-inclusivity.